Determination of the optical constants and film thickness of ZnTe and ZnS thin films in terms of spectrophotometric and spectroscopic ellipsometry. Issue 2 (1st February 2016) - Prakash, Deo; Aboraia, A.M.; El-Hagary, M.; Shaaban, E.R.; Verma, K.D.
Abstract: Zinc telluride (ZnTe) and zinc sulfide (ZnS) thin films were deposited onto glass substrates by the thermal evaporation technique. Their structural characteristics were studied by X-ray diffraction (XRD). XRD showed that both ZnTe and ZnS films are polycrystalline with a zinc blende (cubic) structure. The optical constants ( n, k ), and film thickness ( d ) of ZnTe and ZnS thin films were obtained using two methods, first was based on transmission ( T ) curve obtained by spectrophotometer (SM), using envelope method suggested by Swanepoel and the second was dependent on the ellipsometric parameters ( ψ and Δ) obtained by spectroscopic ellipsometry (SE), using three layer model systems. Both the film thickness and refractive index obtained through these two methods are comparable. The optical band gap was calculated in terms of SE in strong absorption region. The possible optical transition in these films is found to be allowed direct transitions. The increase of E g o p t for both ZnTe and ZnS thin films may be the contributing factor in the increase of crystallites size and decrease in lattice strain.